Theoretical and experimental study on vertical dynamic characteristics of six-axle heavy-haul locomotive on curve - Liu, Peng-Fei; Zhai, Wan-Ming; Wang, Kai-Yun; Feng, Quan-Bao; Chen, Zai-Gang (Transport, 2018)
This paper presents a method to study the vertical dynamic characteristics of a heavy-haul locomotive in curve. A quasi-static analysis model based on the static force equilibrium relationship is established to investigate the load bearing characteristics of suspension system when the locomotive runs through the curve. Then a locomotive–track coupled dynamics model is used to analyse the dynamic characteristics of wheel load in curves. Finally, a field test in curve is carried out to validate the simulated results. The theoretical analysis results indicate that due to the different twist shapes of track on the entry and exit transition curves, for some specific position in the suspension system or wheel arrangements, the corresponding vertical load along the curve length presents an asymmetry about the section of circular curve. The asymmetry is predominantly caused by the Superelevation Angle Differences (SADs) between car body, bogie frames and wheelsets. A distinct phenomenon is that the outer wheel–rail vertical load of the first axle increases when the locomotive enters the transition curve and then reduces when it exits. These results are expected to provide theoretical guidance to the design of the heavy-haul railways. It is suggested that the asymmetric characteristics of the wheel loads can be improved by some measures, such as adopting a low vertical stiffness in the secondary suspension and increasing the transition curve length.First published online 04 May 2016